Technical evaluation of converting starter-sheet copper electrowinning to permanent cathode technology at Anglo American Platinum's Rustenburg base metals refinery - Sole, Kathryn (University of Pretoria, 2025)
Dissertation (MEng (Metallurgical Engineering))--University of Pretoria, 2024.